Optimization of cassava wastewater for efficient starch degradation BY Bacillus sp. strain lfsf-20 - 1995- , author Nur’ain Mohammad Tahir, 614727 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2018